2018
DOI: 10.1021/acs.bioconjchem.8b00514
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-3 Substrates for Noninvasive Pharmacodynamic Imaging of Apoptosis by PET/CT

Abstract: Quantitative imaging of apoptosis in vivo could enable real-time monitoring of acute cell death pathologies such as traumatic brain injury, as well as the efficacy and safety of cancer therapy. Here, we describe the development and validation of F-18-labeled caspase-3 substrates for PET/CT imaging of apoptosis. Preliminary studies identified the O-benzylthreonine-containing substrate 2MP-TbD-AFC as a highly caspase 3-selective and cell-permeable fluorescent reporter. This lead compound was converted into the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 30 publications
0
20
1
Order By: Relevance
“…[ 18 F]TBD is a caspase-3 selective substrate obtained by CuAAC between [ 18 F]FEA and an alkyne precursor, and purified by solid-phase extraction, enabling a fast purification method [ 57 ]. The probe was based on the pan-caspase covalent inhibitor M808, containing two amino acids, aspartic acid and alanine, and the warhead FMK, which was optimized by combinatorial studies [ 58 ].…”
Section: Peptide-based Caspase-3 Probesmentioning
confidence: 99%
“…[ 18 F]TBD is a caspase-3 selective substrate obtained by CuAAC between [ 18 F]FEA and an alkyne precursor, and purified by solid-phase extraction, enabling a fast purification method [ 57 ]. The probe was based on the pan-caspase covalent inhibitor M808, containing two amino acids, aspartic acid and alanine, and the warhead FMK, which was optimized by combinatorial studies [ 58 ].…”
Section: Peptide-based Caspase-3 Probesmentioning
confidence: 99%
“…If CDK1 was knockdown, the pathway of DEPDC1B would be inhibited or blocked, which was consistent the results in other cancers. Caspase3 is a member of the caspase family, which was thought essential regulators in programmed cell apoptosis [ 32 , 33 ]. The cells in hepatoma and various phosphorylated forms can secret IGFBP-6.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, radiolabelled caspase substrates potentially have less susceptibility to saturation and a single enzyme can interact with more than one substrate molecule within the time frame of a PET study, which may result in the amplification of the radioactive signal produced by the active caspase. Various potential substrate candidates have been investigated in preclinical models and intracellular retention of the cleaved radiotracers has been achieved through different strategies, such as intracellular aggregation or the inclusion of cell-penetrating peptides in the molecule [ 49 , 50 , 51 , 52 , 53 ]. Preclinical results have suggested that it is possible to image apoptosis and therapy-induced increases of caspase-3/7 with substrate radiotracers.…”
Section: Discussionmentioning
confidence: 99%